2008
DOI: 10.1038/labinvest.2008.78
|View full text |Cite
|
Sign up to set email alerts
|

Claudin-1 and claudin-2 expression is elevated in inflammatory bowel disease and may contribute to early neoplastic transformation

Abstract: Patients with inflammatory bowel disease (IBD) are at increased risk of developing colorectal adenocarcinoma. The factors that result in IBD-associated carcinogenesis are not understood. We hypothesized that altered expression of intestinal epithelial tight junction proteins might contribute to neoplastic progression. Semi-quantitative immunohistochemical staining of human biopsies was used to assess expression of the tight junction proteins claudin-1, claudin-2, claudin-4, and occludin in IBD, IBD-associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
249
2
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 316 publications
(287 citation statements)
references
References 41 publications
26
249
2
2
Order By: Relevance
“…A growing body of evidence has indicated that cancer progression is associated with decreased tight junctions, and the loss of occludin is generally correlated with tumor development. 34,35 It has also largely demonstrated that EMMPRIN expression is greatly increased in cancer tissues and is correlated with progression and, in some cases, with poor prognosis. 36,37 In view of our results presented here, it is tempting to speculate that EMMPRIN induction during tumor progression may lead to an MMP-dependent cleavage of occludin and may decrease cell contact, thus promoting invasion.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence has indicated that cancer progression is associated with decreased tight junctions, and the loss of occludin is generally correlated with tumor development. 34,35 It has also largely demonstrated that EMMPRIN expression is greatly increased in cancer tissues and is correlated with progression and, in some cases, with poor prognosis. 36,37 In view of our results presented here, it is tempting to speculate that EMMPRIN induction during tumor progression may lead to an MMP-dependent cleavage of occludin and may decrease cell contact, thus promoting invasion.…”
Section: Discussionmentioning
confidence: 99%
“…JAM-A expression was downregulated in UC and in Crohn's disease (CD) at the inflamed mucosa [105]. In contrast, CLDN1 and CLDN2 were reported to be increased in UC and CD [107]. Occludin and CLDN8 were down-regulated and CLDN2 was up-regulated in patients with mild to moderate CD [108].…”
Section: Inflammatory Bowel Disease (Ibd)mentioning
confidence: 99%
“…23 Similar alterations in claudin family members have been described under conditions of inflammation, as seen in the intestinal mucosa of individuals with IBD. 98,99 Furthermore, selective disruption of specific subsets of tight junction proteins can be seen after exposure to inflammatory cytokines. As an example, Figure 5A highlights the effect of exposing cultured epithelial monolayers to the cytokine interferon-g that results in selective disorganization of several tight junction proteins while preserving architecture for the adherens junction proteins E-cadherin and b-catenin.…”
Section: Effects Of Inflammation On Epithelial Cell Functionmentioning
confidence: 99%
“…103 Aberrant claudin, CAR, and JAM-A protein expression has been correlated with cancer progression, altered barrier, and certain inflammatory diseases. 99,104,105 These associations, epithelial functions of junction-associated proteins, have been investigated using forward genetic approaches. These approaches have begun to provide a better appreciation of the consequences of inflammation on the functional biology of many tight and adherens junction molecules as well as desmosomal proteins.…”
Section: Effects Of Inflammation On Epithelial Cell Functionmentioning
confidence: 99%
See 1 more Smart Citation